The effects of elevated water temperatures on adult and juvenile freshwater mussells - Ganser, Alissa M. (My University, 2012)
Native freshwater mussels are long-lived, sessile, benthic invertebrates that may be extremely susceptible to elevated water temperatures because of their patchy distribution, limited dispersal and mobility, and larval dependence on fish. Recent research suggests that many species may be living close to their upper thermal limits and that some rivers have seen a shift in species composition to more thermally tolerant mussel species. We tested the hypothesis that elevated water temperatures (20, 25, 30, and 35C) adversely affected the survival and physiology of juvenile mussels and physiology of adult mussels. In juveniles, the 28-d LT50s ranged from 25.3 to 30.3C. Heart rate was significantly affected by temperature and generally decreased with increasing temperature. Growth rates generally did not vary. In adults, ammonia excretion and oxygen consumption rates after 21-d varied significantly with temperature and generally decreased with increasing temperatures. The O:N ratio varied significantly with temperature in 1 species, as did the tissue condition index. Collectively, these data suggest that juvenile and adult life stages in freshwater mussels can be significantly affected by elevated water temperatures. Estimates of upper thermal tolerances in native mussels are urgently needed because elevated water temperatures caused by global climate change could further challenge already imperiled mussel communities.